Conventions of mathematical problems and their solutions in Hungarian secondary school leaving exams - Kántor, Sándor; K. Fazekas, Anna (Teaching Mathematics and Computer Science, 2011)
Collecting and analyzing the conventions indispensable for interpreting mathematical problems and their solutions correctly assist successful education and objective evaluation. Many professional and didactic questions arose while collecting and analyzing these conventions, which needed clarification, therefore the materials involved concisely in the conventions enrich both the theory and practice of mathematics teaching. In our research we concentrated mainly on the problems and solutions of the Hungarian school leaving examinations at secondary level in mathematics.